Ways of improving the legal regulation of human organ and tissue transplantation in the Russian Federation - E. V. Karakulina; S. M. Khomyakov; O. A. Aleksandrova; I. V. Lysikov; S. V. Shedenko; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2022)
Over the past 10 years, significant breakthroughs have been achieved in Russian transplantology in the field of regulatory legal framework. During this period, the powers of government authorities in the field of healthcare on organization of transplant care and organ donation have been defined, and sources and mechanisms for target financing of medical activities related to organ donation for transplantation purposes have been identified. The procedure for providing medical care under surgery (human organ and/or tissue transplantation) has been adopted, and a state registry system for donor organs, donors and recipients has been created. Measures on organ donation and transplantation in the Russian Federation have been approved within the «Healthcare Development», a framework of the state program of the Russian Federation. The Shumakov National Medical Research Center of Transplantology and Artificial Organs (Shumakov Center) has also been identified as the core institution that coordinates the activities of the entire transplant industry in the Russian Federation. Transplant medical care is currently being provided by specialist physicians trained in human organ and tissue transplantation, in collaboration with other specialist physicians. The Nomenclature of Specialties of Specialists with Higher Medical and Pharmaceutical Education, approved by the Russian Ministry of Health via Order No. 700n of October 7, 2015, does not contain a separate specialty related to human organ and tissue transplantation activities, and this is quite justified. However, in order to improve the legal regulation of transplantation activities, it is necessary to unify the requirements for specialists providing medical care in human organ/tissue transplantation. This can be achieved by developing uniform approaches to the definition of labor functions in the professional standards of specialist doctors involved in transplantation.